2021
DOI: 10.1186/s12974-021-02076-4
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated follicular regulatory T cells and antibody responses exacerbate experimental autoimmune encephalomyelitis

Abstract: Background Follicular regulatory T (TFR) cells are essential for the regulation of germinal center (GC) response and humoral self-tolerance. Dysregulated follicular helper T (TFH) cell-GC-antibody (Ab) response secondary to dysfunctional TFR cells is the root of an array of autoimmune disorders. The contribution of TFR cells to the pathogenesis of multiple sclerosis (MS) and murine experimental autoimmune encephalomyelitis (EAE) remains largely unclear. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 68 publications
2
22
0
Order By: Relevance
“…Besides, adoptive transfer of TFH cells could enhance the disease severity and delay disease remission [ 90 ]. Interestingly, mice with a FOXP3-specific deletion of Blimp1 develop severe EAE and increased TFH-B-Ab response, while having increased frequency of TFR cells [ 104 ]. Most TFH cells were TFH17cells and expressed more IL-17A and GM-CSF, as well as CXCL13 in Prdm1 fl/fl FOXP3 Cre EAE mice [ 104 ].…”
Section: Tfh Cells Tfr Cells and Icos In Multiple Sclerosis And Experimental Autoimmune Encephalomyelitismentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, adoptive transfer of TFH cells could enhance the disease severity and delay disease remission [ 90 ]. Interestingly, mice with a FOXP3-specific deletion of Blimp1 develop severe EAE and increased TFH-B-Ab response, while having increased frequency of TFR cells [ 104 ]. Most TFH cells were TFH17cells and expressed more IL-17A and GM-CSF, as well as CXCL13 in Prdm1 fl/fl FOXP3 Cre EAE mice [ 104 ].…”
Section: Tfh Cells Tfr Cells and Icos In Multiple Sclerosis And Experimental Autoimmune Encephalomyelitismentioning
confidence: 99%
“…Interestingly, mice with a FOXP3-specific deletion of Blimp1 develop severe EAE and increased TFH-B-Ab response, while having increased frequency of TFR cells [ 104 ]. Most TFH cells were TFH17cells and expressed more IL-17A and GM-CSF, as well as CXCL13 in Prdm1 fl/fl FOXP3 Cre EAE mice [ 104 ]. In contrary to WT TFR cells, Blimp1-deleted TFR cells were more encephalitogenic, reflecting dysregulated Ab response and EAE progression [ 104 ].…”
Section: Tfh Cells Tfr Cells and Icos In Multiple Sclerosis And Experimental Autoimmune Encephalomyelitismentioning
confidence: 99%
“…Consistent with the finding that expression of Blimp1 in the thymus is very low and Blimp1 unlikely regulates early T-cell development ( 84 ), mice with a Treg-specific deletion of Blimp1 do not show overt autoimmune phenotype ( 34 , 35 ). However, Tregs from these mice are unstable with reduced Foxp3 expression and produce inflammatory cytokines after immunization, and these mice develop severe experimental autoimmune encephalitis (EAE) ( 34 , 35 , 68 ). At the peak of EAE, the presence of IL-6 activates the DNA methylating enzyme Dnmt3a, resulting in CNS2 methylation.…”
Section: Treg/t Fr Stabilitymentioning
confidence: 99%
“…These unstable T FR cells prematurely migrate into the GC and differentiate into T FH -like cells, resulting in T FH and GC B-cell expansion along with increased antibody and autoantibody production. Furthermore, adoptive transfer of Blimp1-deficient T FR cells can promote pathogenesis associated with dysregulated GC responses ( 34 , 68 ). Taken together, these studies have revealed Blimp1 as a new and central regulator of eTreg and T FR lineage stability and suppressive capacity.…”
Section: Treg/t Fr Stabilitymentioning
confidence: 99%
See 1 more Smart Citation